2020
DOI: 10.3390/biomedicines8090357
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamaldehyde and Hyperthermia Co-Treatment Synergistically Induces ROS-Mediated Apoptosis in ACHN Renal Cell Carcinoma Cells

Abstract: Renal cell carcinoma (RCC) represents the most common form of kidney cancer, which accounts for 3–5% newly diagnosed cancer cases. Since limited therapies are available for RCC, a search for new options is required. Therefore, in this study, we evaluated the combination effect of cinnamaldehyde (CNM) and hyperthermia treatment. CNM treatment combined with 43 °C hyperthermia synergistically increased cytotoxicity in RCC cell line ACHN cells. Through Western blot assays, we observed increased apoptosis signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…This study also sheds light on the downregulation of factors related to metastasis and angiogenesis, such as Cyclin D1, VEGF, and MMP-9, under combined treatment, emphasizing the potential therapeutic promise of this strategy for controlling cancer cell proliferation and metastasis [60][61][62][63]. Importantly, the combined application of AR and 43 • C HT was found to induce cell cycle arrest at the G2/M phase, a process closely associated with the provocation of apoptosis [64,65]. Our findings suggest that the occurrence of apoptosis was dose-dependent under the combined treatment, suggesting the potential for a precise therapeutic approach.…”
Section: Discussionmentioning
confidence: 67%
“…This study also sheds light on the downregulation of factors related to metastasis and angiogenesis, such as Cyclin D1, VEGF, and MMP-9, under combined treatment, emphasizing the potential therapeutic promise of this strategy for controlling cancer cell proliferation and metastasis [60][61][62][63]. Importantly, the combined application of AR and 43 • C HT was found to induce cell cycle arrest at the G2/M phase, a process closely associated with the provocation of apoptosis [64,65]. Our findings suggest that the occurrence of apoptosis was dose-dependent under the combined treatment, suggesting the potential for a precise therapeutic approach.…”
Section: Discussionmentioning
confidence: 67%
“…Physiological reactions of the body to high-temperature stimulation include alterations in membrane permeability or the cytoskeletal system, macromolecule synthesis or intracellular signaling, and DNA repair inhibition [12,13]. In addition, in vitro studies on the combination of hyperthermia with natural products have demonstrated (A) the efficacy of using compounds produced from nature in conjunction with hyperthermia [10,14]. Therefore, we hypothesized that the combination of herbal medications capable of inducing warm or hot qi and hyperthermia might boost the efficacy of hyperthermia treatment of cancer in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…To complement these apoptotic qualities, hyperthermia is often combined with other therapeutic procedures like radiation, chemotherapy, surgery, and immunotherapy [9]. Specifically, natural products may significantly improve the outcome of hyperthermia on cancer cells by acting synergistically and with fewer adverse effects, and in addition is inexpensive [10].…”
Section: Introductionmentioning
confidence: 99%
“…One approach to overcome these limitations is the use of hyperthermia therapy [40]. Cancer hyperthermia therapy involves the use of heat to target and selectively destroy cancer cells [41,42]. However, cancer hyperthermia therapy has limited efficacy when used alone because it induces a heat shock response that activates HSFs and HSPs.…”
Section: Discussionmentioning
confidence: 99%